LARGE SCALE QUALITY ENGINEERING IN DISTANCE LEARNING PROGRAMS - Herron, Rita I.; Holsombach-Ebner, Cinda; Shomate, Alice K.; Szathmary, Kimberly Jo (Online Learning, 2012)
Embry-Riddle Aeronautical University serves more than 36,000 online students across the globe, many of whom are military and other non-traditional students, offering 34 undergraduate, graduate, and professional education/workforce certificate programs, presented both online (Blackboard) and via blended delivery modes. Our highly-centralized model of online course production and management produces and maintains more than 200 turnkey-style courses, including several award winners, which all meet the highest quality standards. Courses are designed by faculty members in partnership with an instructional design production team, working together to ensure course goals and learning objectives are achieved. Then, more than 800+ geographically- dispersed instructors are prepared to facilitate the courses and are monitored and coached throughout each course delivery term. With a student satisfaction rate above 85%, how do we ensure that quality is pervasive at every stage in the distance learning process? In addition, how do we innovate and continue to ensure the quality of design and instruction remains our top priority? The article addresses components of our distance learning model at ERAU-Worldwide, including administration, course design, instructor professional development, and course delivery, all with a focus on how we assure instructional quality at every stage. The people and processes used and how we harness Web 2.0, mobile, and cloud technologies to facilitate distance learning administration, teaching, and learning are detailed.